MEMBUMIKAN PENDIDIKAN MULTIKULTURAL DALAM BINGKAI PENDIDIKAN ISLAM - Zaedun Na’im (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACTThis discussion is about what efforts are made so that in the implementation of Islamic education in educational institutions can be more emphasized and practice the values of cultural diversity that are owned by students. Because this has become very important and very useful for students to further educate the early generations of the nation's future, so that one day they can continue to be embedded in their souls of the importance of respecting cultural diversity in the community so that it will strengthen the unity and integrity of the Indonesian nation. Problems or constraints experienced in the implementation of Islamic education is how to find the right formula or form in the realization of planting and habituation of multicultural values in students themselves. If this can be fulfilled then it will ground multicultural education based on Islamic education then it can be realized. In this study the writer uses qualitative research with a library study approach or library research and is descriptive in nature, where the writer wants to reveal more deeply the concepts or ways in order to realize the slogan or the term "grounding multicultural education within the frame of Islamic education". The results of this study are in an effort to ground this multicultural education based on Islamic education in several ways, namely, First, redesigning the Islamic education curriculum towards being applicable in the cultivation of multicultural education. Secondly, creating conditions so that there will be an awareness of cultural diversity within the school environment, such as holding events or activities that feature the staging of various cultures owned by students, and others. Third, there is a madding or school notice board containing a display of the creativity of students with a cultural themeKeywords: ground multi-cultural education, Islamic education